Investigating best practices for teaching reading recount text in the context of ESP - Rohman, Sandhi Fattahul; Hartiningsih, Sri; Gusdian, Rosalin Ismayoeng (Universitas Muhammadiyah Malang, 2024)
This research investigates the implementation of best practices in teaching reading recount texts within the context of Social Care education at a vocational high school. Recognizing the challenges in conventional learning materials for English for Specific Purposes (ESP) students, this research aims to explore how an English teacher's innovative approach to teaching reading recount text in the field of Social Care. A descriptive qualitative design was employed to describe how the teacher implemented the best practice in teaching reading recount text in the Social Care major. Data collection involved observation and interviews with the English teacher responsible for the Social Care major. The study was conducted at SMK Roudhatul Jannah, chosen for its newly introduced Social Care major in the Indonesian vocational education system. The analysis of the data collected revealed that the teacher's best practice involved focusing on biographies of notable figures in Social Care. The manual creation of biographies allowed the teacher to address the specific needs of the students, fostering engagement and practical application of knowledge. The research concludes that the teacher's proactive approach in manually creating biographies of notable figures not only addresses the limitations of conventional learning materials but also demonstrates a commitment to providing relevant content aligned with the student's major. The findings underscore the importance of ESP teachers adopting innovative teaching methods that resonate with students' specific needs, so it can be beneficial for their future careers.